A Cross-Cultural Comparison of the Academic Engagement of Students. Issue 8 (2nd September 2018) - Shcheglova, I.A.
Abstract : Higher education around the world is undergoing serious transformations as a result of technological, social, and economic processes. Universities from various countries are trying to secure a competitive position for themselves on the international market for educational services. Currently thousands of universities from different countries are trying to enter the race to join the race for international rankings. In their quest to reach the top of the rankings some countries seek to follow the experience of other, more successful nations by adopting their "best" practices. It is not surprising that all countries wish to secure a prosperous future for themselves and take efforts to avoid remaining on the sidelines of world development. However, a factor such as culture or national mentality may undermine the strategies and transformation processes that are being developed. The goal of this study is to conduct a cross-cultural analysis of the academic engagement of students from Russian, Chinese, Japanese, American, and British universities and determine the role that cultural differences play in existing educational systems. The study sample consisted of 26, 648 Bachelor's students who were enrolled at universities in the United States, United Kingdom, China, Japan, and Russia during the 2016–2017 academic year. We used data from the "Student Experience in the Research University" (SERU) international research project to construct an index of student class involvement on the basis of a factor analysis. The results of our univariate analysis of variance (ANOVA) showed that students from Japanese, Chinese, American, British, and Russian universities demonstrate qualitatively different levels of academic involvement, which depends on the organization of the educational process as well as the cultural traditions of these countries. Thus, the Chinese students turned out to be the least engaged, since they were not required to actively participate in class discussions or to discuss additional questions related to the course with the instructor. Russian and American students demonstrated the highest level of engagement compared with other students from countries in the survey. The author emphasizes the need to take into account existing cultural aspects when developing educational strategies, interacting with foreign students in the classroom, as well as conducting comparative studies.